2015
DOI: 10.1097/bot.0000000000000374
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Popliteal Sciatic Nerve Block Versus Single Injection Nerve Block for Ankle Fracture Surgery

Abstract: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 24 publications
1
35
2
Order By: Relevance
“…This may be superior to other studies that reported a displacement rate of 40–50% of sciatic catheters when placed perpendicular to the nerve . Some studies have reported fewer displacements but they did not systematically assess catheter position or function , whereas others consistently tested for catheter function by using loss of cold sensation . By comparison, we found loss of cold sensation corresponding to dermatomes of the common peroneal nerve in 14 out of 16 catheters (88%) after physical exercises and repeat local anaesthetic injection.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…This may be superior to other studies that reported a displacement rate of 40–50% of sciatic catheters when placed perpendicular to the nerve . Some studies have reported fewer displacements but they did not systematically assess catheter position or function , whereas others consistently tested for catheter function by using loss of cold sensation . By comparison, we found loss of cold sensation corresponding to dermatomes of the common peroneal nerve in 14 out of 16 catheters (88%) after physical exercises and repeat local anaesthetic injection.…”
Section: Discussioncontrasting
confidence: 77%
“…The low volumes of local anaesthetic used in this study might increase the possibility of failed block due to imprecise primary placement or secondary displacement. However, despite using a lower volume than previous studies using ultrasound‐guided placement of sciatic catheters (20–40 ml) , we still achieved a high success rate.…”
Section: Discussioncontrasting
confidence: 60%
“…Over the first 72 hours, patients in the CPNB group took significantly fewer oral narcotics and had lower pain scores. 275 Another study of patients undergoing open fixation for calcaneal fractures compared controls (no regional blocks) versus a single-shot block or against a continuous popliteal nerve block. In the 36 hours after surgery, the patients in the continuous block used significantly fewer IV narcotics than did the other 2 groups.…”
Section: Recommendationsmentioning
confidence: 99%
“…Studies on peripheral nerve block in limb surgery raise concerns about ‘rebound pain’ when the effects of the block wear off . This potentially outweighs the benefits.…”
Section: Introductionmentioning
confidence: 99%